Results of Modern Processing of the Photographic Observations of Uranus and Neptune from Archives of UkrVO - Protsyuk, Yu.I.; Kovylianska, O.E.; Protsyuk, S.V.; Yizhakevych, O.M.; Andruk, V.M.; Golovnia, V.V.; Yuldoshev, Q.K. (Science and Innovation, 2024)
The bulk of planet observations was obtained in RI MAO and MAO NASU from 1961 to 1994. Plates from AI UAS were also used. Each plate of NAO was scanned 6 times, in other observatories — only once. All images are processed, most of them are identified and the equatorial coordinates of all objects were obtained. Positional accuracy of the reference stars has value of 0.04"-0.30". Standard deviation of the planets’ position is in the range 0.10-0.12 pixels, that corresponds, depending on the scale, from 0".08 to 0".26. The comparison of the new topocentric positions of the planets with JPL/HORIZONS ephemeris was made. Calculation of (O-C) values and their standard deviation is obtained.